Salicylic Acid: A Double-Edged Sword for Programed Cell Death in Plants - Radojičić, Ana; Li, Xin; Zhang, Yuelin (Frontiers in Plant Science, 2018)
In plants, salicylic acid (SA) plays important roles in regulating immunity and programed cell death. Early studies revealed that increased SA accumulation is associated with the onset of hypersensitive reaction during resistance gene-mediated defense responses. SA was also found to accumulate to high levels in lesion-mimic mutants and in some cases the accumulation of SA is required for the spontaneous cell death phenotype. Meanwhile, high levels of SA have been shown to negatively regulate plant cell death during effector-triggered immunity, suggesting that SA has dual functions in cell death control. The molecular mechanisms of how SA regulates cell death in plants are discussed.